Manufacturing plant performance evaluation by discrete event simulation / Rosli Darmawan ... [et al.] - Darmawan, Rosli; Osman, Mohd Rasid; Mohd Yusuff, Rosnah; Ismail, Napsiah; Leman, Zulkiflle (UPENA, 2004)
A case study was conducted to evaluate the performance of a manufacturing plant using discrete event simulation technique. The study was carried out on an animal feed production plant, Sterifeed Plant at Malaysian Institute for Nuclear Technology Research (MINT), Selangor, Malaysia. The plant was modelled base on the actual manufacturing activities recorded by the operators. The simulation was carried out using a discrete event simulation software. The model was validated by comparing the simulation results with the actual operational data of the plant. The simulation results show some weaknesses with the current plant design and proposals were made to improve the plant performance.